PENGARUH LINGKUNGAN TOKO DAN KECENDERUNGAN BERBELANJA TERHADAP PERILAKU PEMBELIAN IMPULS - Mufti Rahmadi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
This paper aims to explore the process by which four store environment (music, light,employee, and layout) and two individual characteristics (shopping enjoyment tendency(SET) and impulse buying tendency (IBT)) influence impulse buying behavior throughpositive and negative affect, and urge to buy impulsively.The use of these variablesbased on the results of previous studies. The data used in this study are primary data.The research data was obtained by distributing questionnaires to 100 respondents fromthe University of Trisakti. Samper retrieval techniques in this study using purposivesampling. Data analysis tool used is Structural Equation Model (SEM) with AMOS 6.0.Hypothesis testing results show that there are significant Stores environment perceptionof the Positive Affect. Then there is the influence of the Urge Store environtmentperception. And then there is a significant relationship between enjoyment Shoppingtendency towards Positive Affect. Then there is no significant influence of Negative Affecton Urge. Furthermore, a significant difference between the Positive Affect on Urge, anda significant difference between the Urge to Impulse buying. Expected in future studiescan increase the number of independent variables that also can affect Impulse buying.Keywords: Store Environment Tendency, Shopping Enjoyment Tendency, Negative Affect,Positive Affect, Urge, Impulse Buying.